2007
DOI: 10.1103/physrevlett.99.173002
|View full text |Cite
|
Sign up to set email alerts
|

Excited Ions in Intense Femtosecond Laser Pulses: Laser-Induced Recombination

Abstract: Electron-ion recombination in a laser-induced electron recollision is of fundamental importance as the underlying mechanism responsible for the generation of high-harmonic radiation and hence for the production of attosecond pulse trains in the extreme ultraviolet and soft x-ray spectral regions. By using an ion beam target, remotely prepared to be partially in long-lived excited states, the recombination process has for the first time been directly observed and studied. DOI: 10.1103/PhysRevLett.99.173002 PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The highest peak focal intensity for both pulse durations is 10 16 W/cm 2 and lower intensities are sampled by crossing the ion beam with the laser away from the center of the laser focus, that is, shifting the laser focus along its propagation direction while keeping the ion beam position fixed (e.g., Refs. [32][33][34]), a variant of the intensity selective scanning (ISS) method [35,36].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The highest peak focal intensity for both pulse durations is 10 16 W/cm 2 and lower intensities are sampled by crossing the ion beam with the laser away from the center of the laser focus, that is, shifting the laser focus along its propagation direction while keeping the ion beam position fixed (e.g., Refs. [32][33][34]), a variant of the intensity selective scanning (ISS) method [35,36].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This has been used to resolve attosecond timescale motion of molecular dynamics [11][12][13][14]. Electron recombination with the parent ion has been observed by detecting the high-harmonic photons emitted in this process (see, e.g., [15]) or through detection of the particles following the recombination event [16]. Electron recombination is the foundation of the modern era of optical attosecond science [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental evidence, we conclude that the origin of the feature is due to frustrated tunnelling ionization, the first observation of this mechanism in a polyatomic system. Furthermore, we unravel evidence of frustrated tunnelling ionization in dissociation, both two-body breakup to D + D + 2 and D + + D 2 , and three-body breakup to D + + D + D. Gesellschaft processes involving either elastic scattering [6][7][8], inelastic scattering [9, 10], or electron-ion recombination [11]. These phenomena have led to the birth of new areas of research such as high-harmonic generation and attosecond science [12][13][14][15], laser-driven electron diffraction imaging [5][6][7][8], molecular orbital tomography [16,17] and electron wavepacket probing of molecular dynamics [18-21]-naming only a few.Related to the electron recollision process, recently Nubbemeyer et al [22] reported a new phenomenon dubbed frustrated tunnelling ionization (FTI).…”
mentioning
confidence: 99%